Exploring the Challenges of Implementing Universal Health Coverage: A Qualitative Approach - Shirali Kharamin, Salam; Moradian, Mahboubeh (Journal of Foresight and Health Governance, 2024)
This study explores the challenges in implementing Universal Health Coverage (UHC). This qualitative research employed an exploratory design, utilizing semi-structured interviews with 26 participants, including policymakers, healthcare administrators, public health professionals, and frontline providers. Participants were recruited through online announcements and platforms, and interviews were conducted until theoretical saturation was achieved. Thematic analysis was performed using NVivo software to identify key challenges in UHC implementation. The results revealed four major challenges in UHC implementation. Financial barriers were a significant concern, with high out-of-pocket expenditures, insufficient funding, and inefficient resource allocation limiting healthcare accessibility. Infrastructure and service delivery challenges included a shortage of healthcare professionals, unequal distribution of facilities, and inconsistencies in care quality. Policy and governance issues such as weak regulatory frameworks, political instability, and fragmented implementation strategies were identified as key impediments to UHC progress. Socio-cultural and behavioral factors, including public mistrust in health systems, low health literacy, and cultural barriers, further restricted healthcare utilization. These findings highlight the multidimensional nature of UHC challenges, emphasizing the need for comprehensive policy interventions. Achieving UHC requires overcoming financial, infrastructural, policy, and socio-cultural challenges through strategic reforms. Sustainable healthcare financing, enhanced infrastructure investment, governance improvements, and culturally sensitive public health strategies are essential for ensuring equitable healthcare access. Future research should focus on evaluating financing models, digital health solutions, and governance frameworks to enhance UHC implementation globally.